Analyzes of the ICF Domain of Activity After a Neurological Early Mobility Protocol in a Public Hospital in Brazil - Lima, Fernanda dos Santos; Carvalho, Vinícius da Silva; Bittencourt, Inaiacy Souto; Fontana, Ana Paula (Frontiers in Rehabilitation Sciences, 2022)
Background Early Mobility (EM) has been recognized as a feasible and safe intervention that improves functional outcomes in hospitalized patients. The International Classification of Functioning, Disability and Health (ICF) supports understanding of functioning and disability in multidimensional concepts and efforts have been taken to apply ICF in a hospital environment. EM protocols might be linked with the ICF component of activity and participation. The correlations between ICF, EM, and functional scales might help the multidisciplinary team to conduct the best rehabilitation program, according to patients' functional demands. Objectives The primary outcome is to analyze the activity level of neurological inpatients on admission and delivery after a Neurological Early Mobility Protocol (NEMP) at intermediate care settings in a public hospital in Brazil using Activity Level categories, HPMQ, and MBI scores. The secondary outcome is to analyze the ICF performance qualifier, specifically in the activity domain, transposing HPMQ and MBI scores to the corresponding ICF performance qualifiers. Design An international prospective study. Methods NEMP was used to promote patients' mobility during a hospital stay in neurological ward settings. First, patients were categorized according to their Activity Levels (ALs) to determine the NEMP phase to initiate the EM protocol. ALs also were evaluated in the first and last sessions of NEMP. Thereafter, the Hospitalized Patient Mobility Questionnaire (HPMQ) was applied to identify whether patients needed assistance during the performance of hospital activities as well as the Modified Barthel Index (MBI). Both measures were applied in NEMP admission and discharge, and the Wilcoxon Signed Rank Test was used to compare data in these two time points. HPMQ and MBI scores were re-coded in the correspondent ICF performance qualifier. Results Fifty-two patients were included with age of 55 ± 20 (mean ± SD) years and a length of hospital stay of 33 ± 21 days. Patients were classified along ALs categories at the admission/discharge as follows: AL 0 n = 6 (12%)/n = 5 (9%); AL 1 n = 12 (23%)/n = 6 (12%); AL 2 n = 13 (25%)/n = 8 (15%); AL 3 n = 10 (19%)/n = 13 (25%); AL 4 n = 11 (21%)/n = 20 (39%). HPMQ data revealed progressions for the activities of bathing (p < 0.001), feeding (p < 0.001), sitting at the edge of the bed (p < 0.001), sit to stand transition (p < 0.001), orthostatism (p < 0.001) and walking (p < 0.001). Transposing HPMQ activities into ICF performance qualifiers, improvements were shown in bathing (d510.3 to d510.1—severe problem to mild problem) and sitting at the edge of the bed (d4153.2 to d4153.1—moderate problem to mild problem). At MBI score were observed an average of 36 [IQR−35. (95% CI 31.5; 41.1)] on NEMP admission to 52 at discharge [IQR−50 (95% CI 43.2; 60.3)] (p < 0.001). Recoding MBI scores into ICF there were improvements from severe problem (3) to moderate problem (2). Limitations The delay in initiating NEMP compared to the period observed in the literature (24–72 h). The study was carried out at only one center. Conclusions This study suggests that neurological inpatients, in a public hospital in Brazil had low activity levels as could be seen by MBI and HPMQ scores and in the ICF performance qualifier. However, improvements in the evaluated measures and ICF activity domain were found after NEMP. The NEMP protocol has been initiated much longer than 72 h from hospital admission, a distinct window than seen in the literature. This enlargement period could be a new perspective for hospitals that are not able to apply mobility in the earliest 24–72 h.